Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/gcc.22719
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin dynamics governed by a set of nuclear structural proteins

Abstract: During the past three decades, the study of nuclear and chromatin organization has become of great interest. The organization and dynamics of chromatin are directly responsible for many functions including gene regulation, genome replication, and maintenance. In order to better understand the details of these mechanisms, we need to understand the role of specific proteins that take part in these processes. The genome in the nucleus is organized in different length scales, ranging from the bead‐like nucleosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 93 publications
2
20
1
Order By: Relevance
“…Apparently, the CaaX box is not required for this interaction, since the majority of Lamin B was associated with polytene chromosomes in the Lam A25 salivary glands (Figures S5, S6). Other studies suggest that the ⍺-helical rod domain is necessary for the interaction of Lamin B with DNA or histones of the chromatin [3,16,40]. The ⍺-helical rod domain, which is intact in the Lam A25 mutant, may be responsible for colocalization of Lamin B with polytene chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the CaaX box is not required for this interaction, since the majority of Lamin B was associated with polytene chromosomes in the Lam A25 salivary glands (Figures S5, S6). Other studies suggest that the ⍺-helical rod domain is necessary for the interaction of Lamin B with DNA or histones of the chromatin [3,16,40]. The ⍺-helical rod domain, which is intact in the Lam A25 mutant, may be responsible for colocalization of Lamin B with polytene chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies and advanced imaging approaches, including live‐cell studies, have demonstrated that lamin A is responsible for the global long‐range stability of chromatin throughout the whole nuclear space, whereas other structural proteins, such as BAF, Emerin, lamin B, CTCF, and cohesion mildly affect the type of the diffusion, while the extent of motions is not affected . A‐type lamins or a protein complex containing lamin A may generate scaffolds expanding through the nuclear space that regulate many functions, including chromatin organization, gene transcription, DNA replication, DNA damage response, as well as cell cycle progression, cell differentiation, and cell migration . The scaffolding protein SAF‐A interacts with chromatin‐associated RNAs and forms a chromatin mesh in a transcription‐dependent manner .…”
Section: Support Of the Anc‐inc Model With Super‐resolved Fluorescencmentioning
confidence: 99%
“…Much more needs to be learned about the role that lamin A/C and other structural proteins play in cancer cells . A recent review by Sakthivel and Sehgal discusses potential roles of lamin A/C as a tumor biomarker, where increased expression is associated with aggressive colon cancer and higher Gleason scores in prostate cancer.…”
Section: The 3d Nucleus In Cancer Cells: Where We Are Today and Wherementioning
confidence: 99%
“…Lamin A/C are type V intermediate filament proteins that are required for the stability of the nuclear organization. 57,58 Cells from lamin A/C knock-out mice show an altered 3D telomere organization and an increase in genomic instability. 59 Such cells also display enhanced movement of telomeres.…”
Section: Lamin A/cmentioning
confidence: 99%